Caracterización Agro-Morfológica de la línea promisoria UTC 003 de Maíz Chulpi (zea mays l.) en el Barrio Tigualo, Parroquia Panzaleo, Salcedo-Cotopaxi 2020. - Castillo Veloz, Brayan Stalin (2020)
The objective of this research was to characterize agro-morphologically the promising line of chulpi maize (Zea mays L.) UTC 003 through descriptors from the International Maize and Wheat Improvement Centre (CIMMYT), ten plots were implemented in which three plants were taken into complete competition at random for the respective evaluation. Quantitative and qualitative characteristics were evaluated, from the number of days of male flowering to grain evaluation; presenting the following characteristics: the average male flowering was 105 days and the average female flowering of 117 days. In the color of the stem was 10% green and 90% brown. In the deck damage index 33.33% is on scale none, 56.66% in little and 10% in serious. In arrangement of rows was found on the irregular scale. The type of grain that was presented is semi-crystalline, sweet, toothed with a color of 20% yellow and 80% orange. In the index orientation of the leaves was found the 100% pendant. In agronomic characteristics there was an average plant height of 207.3 cm. An average cob height of 97.30 cm. The number of leaves above the cob averages 5.1 and the total number of leaves per plant averaged 12.5. The percentage of corn lodge averaged 4.3% and stem lodge by 5%. The number of rows per cob averages 14.8 with an average weight of 352.8g at 1000 corn kernels. The length of the leaf was presented with an average of 81.7 cm. The length of the spike averaged 84 and the length of the peduncle averaged 12.3 cm. The average primary branches were secondary branches 3.1 and tertiary branches 2.4. The information generated by this research provides farmers with known morphological and agronomic characteristics and can also be considered a good option for carrying out improvement and production programmes.